Mekong, 2100 - Nguyen Duc, Nhat Minh (2018)
The Mekong is one of the most important rivers in the world. It provides livelihood for more than 70 million people in the area, and plays a substantial part in establishing the Mekong Delta, which houses 17.5 million people (2014). However, the river, its basin and the people and animals living there are endangered by aggressive activities from human. At the same time, several large-scale hydroelectricity dam projects are being carried out by governments of upstream countries — which zones the water, traps the sediment, and radically changes the ecosystem — while a group of people downstream are exploiting the sediments to use as building sand — which severely alters the condition of the river bed, changes the current and accelerates erosion. While there are already numerous visual projects celebrating the beauty of the Mekong at the present, few if not none discuss about where the river comes from, how important it has been, the challenges it is facing and what will it be in the future if such challenges continue. “Mekong, 2100” aims to explore a new perspective of a local resident in a narrative format of a tour across time and translate it into Asian-styled illustration series. The delivered result is a series of four illustration books. This report documents the process of the making of the book from the first research to the completion of the first two books and the subordinate soundscape experience, as well as the consideration and rationale behind.